2020
DOI: 10.1002/srin.202000189
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Concept of Hybrid Treatment for High‐Hardenability Steels: Concomitant Hardening and Paraequilibrium Thermochemical Treatment to Produce Interstitially Hardened/Stabilized Austenite Surfaces

Abstract: Steel components' performance requirements are being strongly increased due to the technological evolution of machines. In most of the cases, surface and bulk material requirements are extremely different, so, an optimised component should present different surface and bulk properties. In such a context, the application of surface engineering processes becomes unavoidable and, to achieve the desired performance at acceptable cost, frequently, new materials and/or processing routes are necessary. The novel conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
2
3
0
Order By: Relevance
“…. A double layer comprising a double-structure nitrogen-expanded austenite layer was also recently observed in Toscano et al 53 . According to Toscano et al 53 , the occurrence of this phase indicates the formation of nitrogen-expanded austenite layer with double structure, namely an outermost layer with a higher nitrogen content (varying on the 20-26 at.% N range) and an sublayer with lower nitrogen content (varying on the 4-10 at.% N).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…. A double layer comprising a double-structure nitrogen-expanded austenite layer was also recently observed in Toscano et al 53 . According to Toscano et al 53 , the occurrence of this phase indicates the formation of nitrogen-expanded austenite layer with double structure, namely an outermost layer with a higher nitrogen content (varying on the 20-26 at.% N range) and an sublayer with lower nitrogen content (varying on the 4-10 at.% N).…”
supporting
confidence: 67%
“…A double layer comprising a double-structure nitrogen-expanded austenite layer was also recently observed in Toscano et al 53 . According to Toscano et al 53 , the occurrence of this phase indicates the formation of nitrogen-expanded austenite layer with double structure, namely an outermost layer with a higher nitrogen content (varying on the 20-26 at.% N range) and an sublayer with lower nitrogen content (varying on the 4-10 at.% N). From Williamson et al 54 , it is stated that the γ' N phase formation is caused by stress-assisted diffusion, but here it could be also related to the just transformed ferrite between the outermost γ N phase layer and the non-chemically altered substrate bulk.…”
supporting
confidence: 67%
“…The two studied austenite kinds were the reversed austenite (γ REV ) of the ASTM CA-6NM martensitic stainless steel (MSS), and the thermallystable austenite (γ EST ) of the AISI 304 austenitic stainless steel (ASS). The former typically occurs in the microstructure of ∼620 °C-tempered CA-6NM MSS substrates at 10-30 vol% range, depending on the steel chemical composition [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The latter occurs in solution-treated 304 ASS substrates [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It can also be seen that special attention has been given in the last years aiming to determine the effects of nitriding on the CA-6NM steel surface characteristics [8][9][10][11][12][13]. Such studies have shown that high surface hardness can be achieved in this steel due to formation of phases like nitrogen-expanded austenite, γ′-Fe 4 N and ε-Fe 2-3 N and CrN phases, depending on the nitriding temperature and time and the gas mixture used in the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the influence of the processing parameters studied here, the literature is rich for austenitic stainless steels (ASSs) plasma nitriding [19][20][21][22][23][24][25][26][27][28][29] , but very poor for MSSs, being mainly focused on treated surface characteristics of different materials, through different processes [30][31][32][33][34][35][36][37][38][39][40] . It is to be noted that almost nothing has been published aiming to study such effects on the MSSs LTPC.…”
Section: Introductionmentioning
confidence: 99%